Ultra-large sheet formation by 1D to 2D hierarchical self-assembly of a "rod-coil" graft copolymer with a polyphenylene backbone - Huang, Yinjuan; Yuan, Rui; Xu, Fugui; Mai, Yiyong; Feng, Xinliang; Yan, Deyue (Polymer Chemistry, 2016)
This communication reports a unique ultra-large sheet formation through hierarchical self-assembly of a rod-coil graft copolymer containing a rigid polyphenylene backbone and flexible poly(ethylene oxide) (PEO) side chains. The hierarchical self-assembly process involved a distinctive morphological transition of 1D helical to 2D superstructures. The graft copolymer offers a new chance for the challenging bottom-up fabrication of ultra-large self-assembled nanosheets in solution, as well as a novel system for fundamental studies on 2D self-assembly of polymers.
CRIS-Team Scopus Importer:2023-03-20